Nitrogen Fixation in Tropical Cropping Systems 2001
DOI: 10.1079/9780851994178.0093
|View full text |Cite
|
Sign up to set email alerts
|

Cycling of fixed N in tropical cropping systems.

Abstract: This chapter discusses the major pathways through which fixed N becomes available for use by other plants. The major distinctions between different types of cropping systems (legume-based) and the factors governing amounts of N2 fixed and contributions to cropping system are discussed. In addition, different inputs from N2-fixation in simultaneous systems are also discussed. The beneficial effects of legumes inclusion in cropping systems on soil fertility and erosion control are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
280
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(290 citation statements)
references
References 0 publications
5
280
1
4
Order By: Relevance
“…Chalk 1985;Shearer and Kohl 1986;Witty and Minchin 1988;Peoples and Herridge 1990;Hardarson and Danso 1993;Danso et al 1993;Vessey 1994;Unkovich and Pate 2000;Giller 2001;Peoples et al 2002;Unkovich et al 2008), and associative and freeliving N 2 -fixing agents (Boddey 1987;Chalk 1991;Boddey et al 2001;Giller 2001;Giller and Merckx 2003;Unkovich et al 2008). The N balance and N difference methods provide estimates of N 2 fixation on an area basis, i.e.…”
Section: Measurement Of N 2 Fixationmentioning
confidence: 93%
See 1 more Smart Citation
“…Chalk 1985;Shearer and Kohl 1986;Witty and Minchin 1988;Peoples and Herridge 1990;Hardarson and Danso 1993;Danso et al 1993;Vessey 1994;Unkovich and Pate 2000;Giller 2001;Peoples et al 2002;Unkovich et al 2008), and associative and freeliving N 2 -fixing agents (Boddey 1987;Chalk 1991;Boddey et al 2001;Giller 2001;Giller and Merckx 2003;Unkovich et al 2008). The N balance and N difference methods provide estimates of N 2 fixation on an area basis, i.e.…”
Section: Measurement Of N 2 Fixationmentioning
confidence: 93%
“…The %Ndfa values for the crop legume symbioses in Table 2 were sourced from Peoples et al (2008) in which data from a number of reviews and experimental papers were summarised (Peoples and Craswell 1992;Herridge and Danso 1995;Peoples et al 1995;Wani et al 1995;Jensen 1997;Unkovich et al 1997;Schulz et al 1999;Unkovich and Pate 2000;Giller 2001;Rochester et al 2001;Turpin et al 2002;Aslam et al 2003;Shah et al 2003). Additional information on N 2 fixation of common bean was sourced from Rennie and Kemp (1982a, b) and .…”
Section: Crop Legumes-rhizobiamentioning
confidence: 99%
“…However, there was no consistent relationship between field estimates of P atm and relative growth rates at either 15 or 25°C in liquid medium (Lynch and Smith 1993). Based on an examination of the literature, Giller (2001) concluded that there was little likelihood that the results of laboratory screening of strains for a single stress would have much relevance to field performance. Temperature can also affect the response to inoculation through an effect on competitive performance (Montanez et al 1995).…”
Section: Temperaturementioning
confidence: 98%
“…Fixed N was significantly higher for all strains at 25°C than at 15 or 35°C (Table 2). Giller (2001) concluded that the optimum temperatures for growth and N 2 -fixation vary widely between legume species and reflect their environmental adaptation. This is illustrated by the data of Sangakkara et al (1996a) where the cool-season legume fababean (Vicia faba) failed to nodulate and fix N 2 under a day / night temperature regime of 30 / 23°C, whereas the symbiosis functioned well at 23 / 18°C (Table 3).…”
Section: Temperaturementioning
confidence: 98%
“…cover crops have also been highlighted in earlier studies (Lal et al 1979;Akobundu 1980;Dovonou 1994;Becker and Johnson 1998;Galiba et al 1998). The cover crops manifest this effect through their ability to climb up and shade out weeds within their vicinity (Giller and Wilson 1991). These studies have however been conducted on-station (Tonye et al 1997) and concentrated in West Africa, particularly in Southern Nigeria, where first experiments date back to about four decades for cover cropping and two decades for alley cropping.…”
Section: Introductionmentioning
confidence: 97%